STRATEGI PENANGGULANGAN PERKEMBANGAN PENYALAHGUNAAN NARKOTIKA DI ERA GLOBALISASI - Dwinanda Linchia Levi Heningdyah Nikolas Kusumawardhani (Jurnal Suara Pengabdian 45, 2022)
Globalization has penetrated the territorial boundaries of countries in the world, and has affected the order of people's lives, namely in the political, economic, social, cultural and legal aspects. Indonesia as a part of the world community cannot be separated from these influences, including the influence of the development of narcotics abuse. This paper will discuss the problem of the influence of globalization on the development of narcotics abuse, as well as strategies to deal with the development of narcotics abuse in the era of globalization. The discussion shows that the problem of narcotics abuse seems endless in Indonesia. For this reason, a strategy is needed in overcoming narcotics abuse, namely with pre-emptive, preventive and recessive efforts. Besides that, it is necessary to cooperate with the police of other countries in the form of cooperation between countries, the ASEAN regional area and internationally through the United Nations (UN) through the Interpol forum.